Penerapan Pemberian Aromaterapi Lavender Terhadap Intensitas Nyeri Post Sectio Caesarea di Ruang Adas Manis Rsud Pandan Arang Boyolali - Diyah Wahyu Utami; Panggah Widodo; Ika Silvitasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Sectio Caesarea (SC) delivery is a surgical process to deliver the fetus through an incision in the abdominal wall and uterine wall. Caesarean section delivery is a surgical procedure that can cause pain. Pain during caesarean section will cause unpleasant feelings. Treatment that is often used to reduce pain after caesarean section is by providing pharmacological and non-pharmacological measures. Pharmacological measures, such as administering analgesics, are able to control pain, both moderate pain and severe pain and one of the non-pharmacological treatments to reduce the intensity of the stomach in post-caesarean section patients is by administering lavender aromatherapy to reduce the intensity of pain. The aim of this study was to determine the results of applying lavender aromatherapy to pain intensity in post caesarean section patients in the Adas Manis Room, Pandan Arang Hospital, Boyolali. This research is descriptive research using a case study approach. The subjects in this study were 2 post caesarean section patients. The application of lavender aroma therapy in this study was carried out in accordance with the SOP for lavender aroma therapy, the application was carried out for 3 days with a frequency of application once a day within 10 minutes. The instrument for measuring pain intensity uses the Numeric Rating Scale (NRS). After being given lavender aromatherapy once a day for 3 days, there was a decrease in the pain scale from moderate pain scale to mild pain scale in both respondents. Lavender aromatherapy can be used as a non-pharmacological technique or independent intervention to reduce pain intensity in post-cesarean section patients.